Lighting analysis in mosque architecture in Malaysia - Foroughmand, Mostafa; Ismail, Sumarni; Utaberta, Nangkula; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, 2015)
The appropriate design and mixture of daylighting techniques can significantly help in improving the interior space design. Light plays an important role in famous mosques around the world but it is ignored in new built mosques of malaysia to make a dynamic feeling and sense of god’s presence in the religious space. It is proved that natural daylight design with light hierarchy and harmony has an important role in interior environment which is beable to make the human to reach the sense of serenity and concentration. The main aim of this study is to investigate and review the fundamental aspects of daylighting for evaluating how daylight as a sacred element was used in implicated mosques. For this reason firstly we analaysed the mosque prayer hall by collected datas from literature and observation to evaluate the current situation. The results indicate that the openings for daylight entrance should be designed in a way to achieve hierarchy, harmony and designed patterns with daylight during the pray time in the prayer hall. Methods, techniques and designs which have discussed in this paper are suggested solutions for pupose of enhancing sense of sacred by using natural daylighting in mosque prayer hall.